Media Hegemony and the Suppression of Counter-Hegemony in Nigeria - Garison, Anthony; Yakubu, Dangana Deborah; Tsokwa, Solomon Blessing (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Media are realized to be the powerful tools in the dissemination and reinforcement of dominant ideologies in order to maintain the status quo thereby serving the interest of the powerful groups at the detriment of the nation’s social justice, economic equality and national development. This study therefore, examines the phenomenon of media hegemony and its impact on the suppression of counter-hegemony in Nigeria. Using Antonio Gramsci's concept of hegemony as a framework, this research investigates how the dominant media landscape in Nigeria reinforces existing power structures, marginalizes alternative voices, and limits the emergence of counter-hegemonic narratives. Through a critical discourse analysis of media operations in Nigeria, their orientations and contents. The study reveals the ways in which media hegemony is maintained and contested in Nigeria. The concentration of media ownership, censorship, and the manipulation of public opinion are key strategies used to suppress counter-hegemony in Nigeria. Furthermore, the study highlights the challenges faced by alternative voices and social movements in promoting counter-hegemonic discourses and resisting dominant narratives. The research contributes to our understanding of the complex dynamics of media hegemony, how media shape power structures, normalizes the views of the ruling class and suppress counter-hegemony in Nigeria; and underscores the need for a more inclusive and diverse media landscape that promotes critical thinking, democratic participation, social equality and social justice.